A dual-wavelength Q-switched fiber laser based on reduced graphene oxides. (11th April 2019) - Su, Yulong; Huang, Xinning; Hu, Hui; Wen, Yu; Xie, Xiaoping; Si, Jinhai; Wang, Yishan; Zhao, Wei
Abstract: This report demonstrates a dual-wavelength stable Q -switched Er-doped fiber (EDF) laser with a reduced graphene oxide (rGO)-based saturable absorber. The rGO is prepared by depositing the graphene oxide on fluorine mica (FM) using a thermal reduction method. The modulation depth and saturable intensity of rGO/FM are measured to be 5.8% and 73.6 MW cm −2 . By employing the rGO/FM film in the EDF laser cavity, stable dual-wavelength Q -switching operation is achieved. The two wavelength peaks locate at 1531.84 nm and 1558.14 nm. The shortest pulse duration is 1.83 µ s. The maximum output power is measured to be 14.65 mW, corresponding to the maximum single pulse energy of 154.34 nJ. The experimental results evidently show that the rGO is a promising type of nonlinear material.